CORRELATION ANALYSIS, CONFORMITY MATRIX, AND TRANSITION STRATEGY FROM ISO 9001:2015 TO ISO 9001:2026 IN THE IMPLEMENTATION OF A MODERN QUALITY MANAGEMENT SYSTEM (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
ISO 9001 is the most widely used international standard for implementing Quality Management Systems (QMS) across various industrial and service sectors. Since the publication of ISO 9001:2015, organizations worldwide have adopted a risk-based approach, a process approach, and the Plan-Do-Check-Act (PDCA) cycle as the foundation for continuous quality improvement. As the global business environment evolves, characterized by digital transformation, climate change, increasing stakeholder demands, and the emergence of hybrid and remote work patterns, the International Organization for Standardization (ISO) is revising the standard, which is planned to be published as ISO 9001:2026. This study aims to analyze the correlation between ISO 9001:2015 and ISO 9001:2026, compile a conformity matrix between clauses, identify new requirements emerging in the revised draft, and formulate transition strategies that organizations can implement. The research method uses a descriptive qualitative approach through a documentation study of ISO 9001:2015, the Committee Draft ISO 9001:2026, and various supporting documents related to the standard revision process. The research results show that the main structure of the High Level Structure (HLS) remains intact, so organizations that have implemented ISO 9001:2015 do not face fundamental changes. However, the 2026 revision introduces several important reinforcements, including consideration of climate change, quality culture, ethical behavior, hybrid work environment management, strengthened change management, and the separation of risk and opportunity management. These findings suggest that organizations need to conduct gap assessments, update documentation, improve personnel competency, and adjust internal audit mechanisms to ensure readiness for the transition to ISO 9001:2026.